To Outsource or Not to Outsource: Resource Decision-Making in the Project Management Environment - Blair, Garry; Woodcock, Helen; Pagano, Rosane (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2023)
Every organisation engages in some form of outsourcing in order to sustain their operations. The decision to outsource certain functions and the selection of the optimum providers is an important aspect of organisational strategy. Failure in respect of outsourcing could have a critical effect on an organisation, leading to losses and ultimately its termination. Failure to utilise the most efficient and effective option can also lead to problems, as competitors may improve their relative position and remove business from the organisation. The key factors in making decisions to outsource activities are discussed. The importance of the features of the organisation and its context are emphasised. The rationale behind outsourcing is mentioned, principally this concerns the supply of products or services that the organisation would prefer not to make or perform, for various reasons. The form of the contract between the provider and client is also studied, in order to discern the key features. The option of global sourcing is considered. Organisations can move all or some of their activities overseas, termed offshoring. This paper considers outsourcing in respect of technology. The area of cloud computing is discussed, as both an illustration and a key mechanism for the provision of outsourced IT services. A thematic analysis of selected, key literatures is undertaken. A summary of factors related to outsourcing decision-making and contract formulation is provided, in order to assist practice and constitute a focus for further research. The principal facets of an outsourcing contract are identified, utilising an empirical study. How to cite this article:  Blair G, Woodcock H, Pagano R. To Outsource or Not to Outsource: Resource Decision-Making in the Project Management Environment. J Adv Res Alt Energ Env Eco 2022; 9(3&4): 10-20.